A Paradigm Shift from Optimal Play to Mental Comfort: A Perspective from the Game Refinement Theory - Hiroyuki Iida; Mohd Nor Akmal Khalid (Universitas Komputer Indonesia, 2020)
The game refinement theory focuses on the game designer perspective, where its application in various types of games provides evidence of the occurring paradigm shift. Utilizing the logistical model of game outcome uncertainty, it provides a platform for incorporating gamified experience observed in games to be adopted in domains outside of game while retaining the context of the game. Making games as a testbed, the implications of the game refinement theory have been observed in the educational and business perspective, while further explored its utility in interpreting some states of the human mind. In addition, a holistic view of design in games and in the real-world environments was discussed, where the prospects of the game refinement theory were also highlighted.